Different characteristics of cryptococcal meningitis between HIV-infected and HIV-uninfected patients in the Southwest of China. (8th September 2016) - Liu, Ya; Kang, Mei; Wu, Si-Ying; Ma, Ying; Chen, Zhi-Xing; Xie, Yi; Tang, Jiang-Tao
Abstract: Cryptococcus is the major pathogen that causes fungal meningitis. In the People's Republic of China, especially in the Southwest area, cryptococcal meningitis (CM) in HIV-uninfected patients is more common than in HIV-infected patients. We compared clinical features and laboratory data pertaining to CM in patients with different immunological statuses. Demographic data, clinical manifestations, and laboratory data from inpatients in West China Hospital Sichuan University were collected from June 2009 to June 2014. Patients were grouped according to HIV status. Continuous variables were evaluated by Student t -test or Wilcoxon rank sum tests. Categorical variables were analyzed by χ 2 test. Among 85 patients with CM were identified, 53 (62.4%) were HIV-uninfected patients. CM occurred more frequently in males in the HIV-infected group. Compared with HIV-infected patients, HIV-uninfected patients had more leukocytes in their blood and more leukocytes and protein in cerebrospinal fluid. More HIV-uninfected patients had increased cerebrospinal fluid (CSF)/serum albumin ratios, while intrathecal immunoglobulin G (IgG) synthesis was significantly increased. The rate of in-hospital mortality of HIV-infected CM patients was higher. Clinical signs are similar between HIV-uninfected and HIV-infected CM patients. Fewer leukocytes and protein was detected in the CSF and lower local synthesis of IgG in the central nervous system in HIV-infected patients, which reflects their diminished immune response. These characteristics should be noted in order to avoid misdiagnosis. Meningeal enhancement and intrathecal IgG synthesis in the HIV-uninfected group was significantly higher, that may be performance of aggressive inflammatory response and might contribute to a better outcome.